Prospect of the Hofburg castle, seen from the outside towards the exit - Kleiner, Salomon, 1700-1761 (artist):::Creator::::::::::::; Corvinus, Johann August, 1683-1738 (engraver):::Contributor:::::::::::: (Johann Andreas Pfeffel)
Color engraving of the imperial palace in Vienna